A combined experimental and theoretical study of the lowest-lying valence, Rydberg and ionic electronic states of 2, 4, 6-trichloroanisole. (September 2021) - Kumar, S.; Duflot, D.; Hoffmann, S.V.; Jones, N.C.; Bolognesi, P.; Carlini, L.; Richter, R.; Avaldi, L.; Brunger, M.J.; Limão-Vieira, P.
Highlights: The first complete study to date of the VUV electronic spectroscopy of TCA in the 4.0–10.8 eV energy range, with the most reliable and complete set of absolute photoabsorption cross-sections for this region being given. The observed low energy structure has been assigned to valence, Rydberg and mixed valence/Rydberg transitions. Theoretical calculations on the vertical excitation energies and oscillator strengths and the lowest-lying ionic states were performed using different levels of accuracy methods. Novel photoelectron spectrum of the lowest-lying ioinic states with their related assignments. Abstract: We investigate for the first time the gas-phase lowest-lying valence, Rydberg and ionic electronic states of 2, 4, 6-trichloroanisole (TCA) using synchrotron radiation for photoabsorption and photoelectron spectroscopy. The high-resolution vacuum ultraviolet photoabsorption spectrum, in the 4.0–10.8 eV energy-range, has been measured with absolute photoabsorption cross-sections and, thanks to novel ab initio calculations of the vertical energies and oscillator strengths, an assignment of the electronic transitions is comprehensively reported. The assignment of weak vibrational features in the absorption bands of TCA reveal that the ring and C–Cl stretching modes are mainly active. In the photoelectron spectrum the lowest 18 ionic bands, between 8 and 30 eV, have been observed and assigned using the first set of calculated valence and outer valence vertical ionisation energies. Finally, the measured absolute photoabsorption cross sections have also been used to estimate the photolysis lifetime of TCA in the upper stratosphere (20–50 km).